Padrões de fluorescência em uma coleção de Didelphidae paraguaios - Smith, Paul; Hicks, George (Brazilian Journal of Mammalogy, 2024)
Many species of opossum (Didelphimorphia) are known to fluoresce, but the significance of this characteristic is unclear. In the interests of contributing to the faunal inventory of fluorescence in Didelphids, we examined 62 specimens of 10 species of Paraguayan opossums under a UV light and describe the patterns observed. Of particular interest is a clear apparent difference in fluorescence between two cryptic and occasionally sympatric species, Marmosa rapposa and Marmosa paraguayana which may be a potential isolating mechanism. Furthermore, we suggest the possibility that fluorescence declines with time since collection in Didelphis albiventris, and the fluorescence in that species is not related to age or sex. While the significance of fluorescence in Didelphids remains obscure, patterns observed show some degree of species specificity within the geographic boundaries of this study.